2020
DOI: 10.1111/pce.13731
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale approach reveals regulatory players of water stress responses in seeds during germination

Abstract: Seed germination is regulated by environmental factors, particularly water availability. Water deficits at the time of sowing impair the establishment of crop plants.Transcriptome and proteome profiling was used to document the responses of sunflower (Helianthus annuus) seeds to moderate water stress during germination in two hybrids that are nominally classed as drought sensitive and drought tolerant. Differences in the water stress-dependent accumulation reactive oxygen species and antioxidant enzymes activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Several temperatures (5,10,15,20,25,30 and 35 • C) were applied to the seeds of the 44 genotypes during germination tests on water (Table S1). Figure 2, comparing germination percentages of seeds of SOLQUA-160 and SOLQUA-165, shows that both genotypes can germinate to 100% between 10 and 25 • C, which correspond to optimal temperatures for sunflower seed germination.…”
Section: Effect Of Temperature Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Several temperatures (5,10,15,20,25,30 and 35 • C) were applied to the seeds of the 44 genotypes during germination tests on water (Table S1). Figure 2, comparing germination percentages of seeds of SOLQUA-160 and SOLQUA-165, shows that both genotypes can germinate to 100% between 10 and 25 • C, which correspond to optimal temperatures for sunflower seed germination.…”
Section: Effect Of Temperature Stressmentioning
confidence: 99%
“…In the last decades, molecular aspects of seed dormancy and germination have been reported in different species (for review [11][12][13]) and in sunflower in particular [14][15][16][17]. Several genes have been related to seed vigor [18][19][20], but, they can hardly be used as vigor genetic markers. The quantitative trait loci (QTL) approach allows the identification of loci that influence seed vigor in Brassica oleracea, such as speed of germination (SOG1), which contains two genes related to abscisic acid that influence negatively the speed of germination [21][22][23].…”
mentioning
confidence: 99%
“…Germination is an essential developmental stage change in the life cycle of a plant, which plays an important role in crop establishment and environmental adaptation (Liu et al, 2019). Germination and early stage of growth are most sensitive to environmental stresses, particularly drought and high temperature (Saux et al, 2020;Shahrajabian et al, 2020). Numerous studies have examined the inhibition of seed germination and seedling establishment as a result of heat and drought stress in several crops (Shaban, 2013;Wen, 2015;Saberali and Shirmohamadi-Aliakbarkhani, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased water potential is a general consequence of drought, which has negative effects on germination and consequent seedling growth (Shahrajabian et al, 2017). The disturbance of water availability during germination may induce erratic and decreased germination, leading to poor stand establishment (Saux et al, 2020). Furthermore, drought stress can delay, reduce, or inhibit germination and seedling vigor of wheat cultivars (Jovović et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recognizing the criteria of seed germination and seedling establishment for threatened species used in reintroduction projects is crucial to ensuring artificial seedling propagation (Ren et al 2014). It has been shown that imbibition is an important trigger for seed germination and several species require light for high germination rates (Hegarty 1978;Bell 1999;Saux et al 2020). Soil type is also an important factor influencing seed germination and growth (Iralu et al 2019).…”
Section: Introductionmentioning
confidence: 99%